2003
DOI: 10.1097/01.lab.0000088767.45565.27
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Skin Tumors by Magnetic Resonance Imaging

Abstract: SUMMARY:In vivo magnetic resonance imaging (MRI) is a powerful noninvasive technique in medical diagnosis; however, its application to analyze skin disorders is still at initial stages. To check whether MRI can be used as a noninvasive tool to analyze skin tumors, we carried out MRI of mice after treatment with benzo[a]pyrene (BP), a well known carcinogen. MRI was done on whole mice and was particularly focused on various layers and regions of interest of the skin: dermis, epidermis, and tumor. Initial MRIs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, the introduction of microscopy surface coils has enabled its use in the evaluation of more superficial structures with better image quality and high resolution (1). Numerous studies have shown the usefulness of high-resolution MRI with microscopy coils (HR-MRI) in the evaluation of patellar cartilage, soft tissue tumors of the hand and foot, and ocular lesions including ocular melanomas (2-4).…”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of microscopy surface coils has enabled its use in the evaluation of more superficial structures with better image quality and high resolution (1). Numerous studies have shown the usefulness of high-resolution MRI with microscopy coils (HR-MRI) in the evaluation of patellar cartilage, soft tissue tumors of the hand and foot, and ocular lesions including ocular melanomas (2-4).…”
Section: Introductionmentioning
confidence: 99%
“…Because such observation depends on personal experience of the physician, lesions may be falsely considered benign, may not undergo biopsy, and therefore may not be subjected to the reference diagnostic gold standard i.e. histo-pathology [2]. Currently, full diagnosis of suspicious skin lesions implies excision-biopsy of the lesion followed by anatomo-pathological examination.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MRI of the skin surface requires an enlarged field of view and increased sensitivity, lending itself to potential inaccuracy in determination of the margins of the subcutaneous tissues, and possible inaccurate estimation of the depth from skin to epidural space. 19 …”
Section: Discussionmentioning
confidence: 99%